A multi-criteria-based procedure for the robust definition of algorithms aimed at fast seismic risk assessment of existing RC buildings. (April 2020) - Sangiorgio, Valentino; Uva, Giuseppina; Aiello, Maria Antonietta
Abstract: After emergency events like severe earthquakes, the structural performance targets and civil protection provisions require that existing strategic buildings must be fully operational, whereas common buildings must avoid collapse and ensure correct evacuation. The observation of post-earthquakes damages has shown that the performance of existing buildings and their functionality after an earthquake are related not only to structural damage but also to damage that occurs to nonstructural elements, systems, installations and furniture. In addition, if adequate guidelines, training and evacuation procedures are provided, the emergencies can be better faced safeguarding the users health. To this aim for a large-scale mapping of the seismic risk in existing building the performance of non-structural elements and equipment should be taken into account in new fast seismic risk evaluation procedure. In this paper, an Analytic Hierarchy Process based procedure is applied to indirect risk assessment method for reinforced concrete structures such as the Rapid Visual Surveys, to obtain a robust Risk Index. The main novelty of this approach regards the application of a Multi-Criteria Analysis in order to take into account qualitative and quantitative data, including the effectiveness of guidelines, training and evacuation procedures, involved in the index evaluation (more than 80 parameters). Moreover, a state-of-the-art sensitivity analysis is applied to overcome the robustness issue of the Risk Index by exploiting the theory of Multi-Criteria methods. Finally, in order to test the effectiveness of the method, the resulting Index is compared with the RVS method and a TOPSIS-based risk assessment through the application to 4 case studies.